(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
This article is about the game For more information, see the Death of a Salesman and the American Dream. Saleman’s Death is a 1949 stage play written by American playwright Arthur Miller. The game was shown on Broadway in February 1949, running 742 games. It is a two-act tragedy set in 1940 in New York told in terms of memories, dreams and controversies of leading character Willy Loman, a traveling merchant who is disappointed with his life and seems to be slipping into the military. The game contains many powerful themes, such as the American Dream, reality, and betrayal. It examines the psychological turmoil of the protagonist and the impact of capitalist society on his life. Received the Pulitzer Prize for Drama and the 1949 Tony Award for Best Play. It is considered by some critics to be one of the greatest games of the 20th century.